SOSIALISASI BUKU KIA EDISI REVISI TAHUN 2020 BAGI IBU HAMIL DAN PEMERHATI KESEHATAN DI DESA TAMANSARI MUMBULSARI JEMBER - Ai Nur Zannah; Melati P. Sari (Jurnal SADEWA, 2023)
Jember Regency is the region in East Java with the most maternal deaths (IMR), with 115 maternal mortality and a high infant mortality rate in 2021. Based on acquired preliminary data from Tamansari Village cadres, it was found that: there are still KIA books stored in the cadre with the reason that it will not be damaged and when the mother checks, there is no reason to forget to bring the book, so that the majority of mothers do not know what is written in the KIA book. The objective of this service project is to Socialization of the KIA Book Revised Edition 2020 to Pregnant Woman and Health Observers in Tamansari Village, Mumbulsari District, Jember Regency. The target of socialization is pregnant women and health observers, totaling 22 pregnant women, 4 cadres and 1 community figure. Of the 22 pregnant women who participated, 17 people (77,3%) increase knowledge from pre-test to post-test with all able to answer the questions given, while 5 people (22,7%) still can't answer the question. The knowledge of all health observers increased from pre-test to post-test (100%). Based on the findings, it can be said that the socialization sessions are quite beneficial at enhancing the knowledge of women who are pregnant and health observers.